Experimental and Numerical Simulation of the Dynamic Frictional Contact between an Aircraft Tire Rubber and a Rough Surface - Iulian Rosu; Hélène L. Elias-Birembaux; Frédéric Lebon; Hagen Lind; Matthias Wangenheim (Lubricants, 2016)
This paper presents a numerical simulation of an aircraft tire in contact with a rough surface using a variable friction coefficient dependent on temperature and contact pressure. A sliding facility was used in order to evaluate this dependence of the friction coefficient. The temperature diffusion throughout the tire cross-section was measured by means of thermocouples. Both frictional heating and temperature diffusion were compared to numerical two- and three- dimensional simulations. An adequate temperature prediction could be obtained. In future simulations, wear should be taken into account in order to have a more accurate simulation especially in the case of high pressures and slipping velocities. A 3D finite element model for a rolling tire at a velocity of 37.79 knots (19.44 m/s) and in a cornering phase was investigated using a variable friction coefficient dependent on temperature and pressure. The numerical simulation tended to predict the temperature of the tire tread after a few seconds of rolling in skidding position, the temperature of the contact zone increases to 140 °C. Further investigations must be carried out in order to obtain the evolution of the temperature observed experimentally. The authors would like to point out that for confidentiality reasons, certain numerical data could not be revealed.